Organizational and technological principles of building condition monitoring at the stage of life cycle operation - S. V. Fedosov; A. A. Lapidus; A. B. Petrukhin; B. E. Narmaniya (Vestnik MGSU)
Introduction. There is no concept of “life cycle of a building structure (building material)” in the available regulatory and scientific and technical literature. Since the duration of the life cycle of a real estate object largely depends on the durability of building structures and materials, it is reasonable to study the changes in the strength parameters of building structures during their life cycle. Graphical modelling of the life cycle of a building structure (building material) reflects the strength parameters of the structure at all stages of operation.Materials and methods. The methodology of the work is based on graphical modelling of the life cycle of a building structure. The relative value of compressive strength coefficient was chosen as an indicator of the concrete structure durability. The change of the compressive strength of concrete building structures can be determined according to the logarithmic law. The mathematical operator of the Cauchy problem, which consists in finding a solution to an ordinary differential equation of the first order, can be used to establish the state of a concrete structure at any period of the life cycle.Results. Graphical models of compressive strength behavior in time of the life cycle of a structure (building) are presented, showing the periods of formation of the concrete structure. The graphical model is supplemented with the period of time up to the moment corresponding to the achievement of the critical value of concrete strength, at which the structure collapses. The variants of changing the life cycle of the structure under the influence of external and internal factors are graphically depicted.Conclusions. The definition of the life cycle of a building structure (material) is proposed. The expediency of introducing the concept of “life cycle of a building structure (building material)” into regulatory documentation and scientific and technical literature is substantiated.